PERSONAL PLANNER (PERPLAN)-MOBILE APPLICATION - KEVEENNIYA, MANOKARAN (Universiti Malaysia Sarawak, (UNIMAS), 2021)
This project is a mobile application called PerPlan. The main purpose of developing the PerPlan is to cater features like tracking activities daily or monthly, managing and tracking finances of events as well as generating graphs to visualize the finances of an event in one platform instead of alternating apps back and forth for these features. There are also features that enable the user to retrieve backdated activities in the system with a simple search mechanism. This search mechanism, in turn, will fetch details according to the types of activities from the database. Besides that, there are challenges in the proposed project which are structuring logic for tracking daily activities, managing finances based on existing events, and appropriate graphs to visualize data. The existing issues of digital planners in the current market is the stepping stone to the development of PerPlan. Issues such as free limited features for usage like Google Calendar or orientated toward project management like Trello. User from different background or field of work finds it difficult to comprehend how to use these planners. Free accounts can only be used for a specific timeframe. Thus, these are the reasons which have contributed to the development of this project. In order to solve these issues, the PerPlan app is the solution since it is designed in a way that has the capability to resolve most of the issues. For a user to utilize the offered features in this project, they are required to have a registered account in the system. PerPlan is built using the Rapid Application Development method since it does not consume time as much as other approaches. This method is chosen because it is iterative in nature and able to support application development in a short timeframe. It also allows the developer to make changes as the project progresses which affects the project schedule.